Revolutionizing supermarket checkout: A comprehensive review of Radio Frequency Identification (RFID)-enabled shopping carts for automatic payments and real-time inventory tracking - Vlachos, Marios (Trends in Computer Science and Information Technology, 2024)
This paper provides an in-depth exploration of Radio Frequency Identification (RFID)-enabled shopping carts, a novel solution tailored for automatic payments and real-time inventory tracking in supermarkets. Through the integration of RFID technology into shopping carts, these systems update the cart’s contents automatically as products are added, thus optimizing checkout processes and improving operational effectiveness. The review delves into the fundamental technology, advantages, obstacles, and potential uses of RFID-enabled shopping carts in the retail sector, offering insights into implementation factors and avenues for future research.